2021
DOI: 10.1038/s41467-021-25235-w
|View full text |Cite
|
Sign up to set email alerts
|

Decline in plankton diversity and carbon flux with reduced sea ice extent along the Western Antarctic Peninsula

Abstract: Since the middle of the past century, the Western Antarctic Peninsula has warmed rapidly with a significant loss of sea ice but the impacts on plankton biodiversity and carbon cycling remain an open question. Here, using a 5-year dataset of eukaryotic plankton DNA metabarcoding, we assess changes in biodiversity and net community production in this region. Our results show that sea-ice extent is a dominant factor influencing eukaryotic plankton community composition, biodiversity, and net community production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 53 publications
7
36
0
Order By: Relevance
“…Overall, the diversity (richness and Chao1 index; Supplementary Figure 2A ), assessed using 18S rRNA, was comparable to what was previously reported in other parts of the world ocean ( de Vargas et al, 2015 ) and in the same region in other periods of the year ( Lin et al, 2021 ). As noted previously, the spring corresponds to a low abundance of protists ( Trefault et al, 2021 ), although, Arrigo et al (2017) reported some areas of relatively high chlorophyll in early spring.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Overall, the diversity (richness and Chao1 index; Supplementary Figure 2A ), assessed using 18S rRNA, was comparable to what was previously reported in other parts of the world ocean ( de Vargas et al, 2015 ) and in the same region in other periods of the year ( Lin et al, 2021 ). As noted previously, the spring corresponds to a low abundance of protists ( Trefault et al, 2021 ), although, Arrigo et al (2017) reported some areas of relatively high chlorophyll in early spring.…”
Section: Discussionsupporting
confidence: 86%
“…Overall, the mixed layer was deeper than the chlorophyl maximum depth across the cruise, explaining the relative similarity between the samples taken at the sub-surface and at the DCM layer regarding both environmental parameters and planktonic community ( Table 1 and Figures 1B,C ). As noted above, reduced sea ice has been identified as a good predictor of net community production ( Lin et al, 2021 ). The decrease in coverage and duration of sea ice observed prior to 2008 reversed temporarily and began increasing ( Ducklow et al, 2013 ; Schofield et al, 2018 ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations